Non-Invasive Remote Ischemic Preconditioning May Protect the Gastric Mucosa Against Ischemia-Reperfusion-Induced Injury Through Involvement of Glucocorticoids - Ludmila Filaretova; Olga Komkova; Maria Sudalina; Natalia Yarushkina (Frontiers Media S.A., 2021)
Remote ischemic preconditioning (RIPC) is one of the most effective approaches to attenuate tissue injury caused by severe ischemia-reperfusion (I/R). Experimental studies have demonstrated that RIPC is capable of producing a protective effect not only on heart, but also on brain, lungs, kidneys, liver, intestine, and stomach. We previously demonstrated that glucocorticoids participate in protective effect of local gastric ischemic preconditioning against I/R-induced gastric injury. In the present study we investigated whether RIPC may protect the gastric mucosa against I/R-induced injury through involvement of glucocorticoids. Anesthetized fasted Sprague Dawley male rats were exposed to prolonged gastric I/R (30 min occlusion of celiac artery followed by 3 h of reperfusion) alone or with preliminary brief RIPC (10 min non-invasive occlusion of right hind limb blood flow followed by reperfusion for 30 min). First, we investigated the effect of RIPC on I/R-induced injury by itself. Then to study the role of glucocorticoids similar experiments were carried out: 1) in rats pretreated with the inhibitor of glucocorticoid synthesis, metyrapone (30 mg/kg, i.p), and in control animals; 2) in adrenalectomized rats without or with corticosterone replacement (4 mg/kg, s.c.) and in sham-operated animals; 3) in rats pretreated with glucocorticoid receptor antagonist RU-38486 (20 mg/kg, s.c.) and in control animals. I/R induced corticosterone rise and resulted in the gastric erosion formation. RIPC significantly reduced the erosion area in control animals. Metyrapone injected shortly before RIPC caused a decrease in plasma corticosterone levels and prevented the gastroprotective effect of RIPC and, moreover, further aggravated the deleterious effect of I/R. Adrenalectomy performed 1 week before experiment created long-lasting corticosterone deficiency and had no effect on the gastroprotective effect of RIPC. Nevertheless, corticosterone replacement which mimics the corticosterone rise, similar to RIPS, significantly reduced erosion areas of gastric mucosa in adrenalectomized rats supporting the role of glucocorticoids in gastroprotection. RU-38486, which occupied glucocorticoid receptors, similar to metyrapone prevented the gastroprotective effect of RIPC and, moreover, further aggravated the deleterious effect of I/R. The results of the present study demonstrate for the first time that RIPC may protect the gastric mucosa against I/R-induced injury through involvement of glucocorticoids.